2000
DOI: 10.1093/toxsci/54.1.138
|View full text |Cite
|
Sign up to set email alerts
|

The Estrogen Receptor Relative Binding Affinities of 188 Natural and Xenochemicals: Structural Diversity of Ligands

Abstract: We have utilized a validated (standardized) estrogen receptor (ER) competitive-binding assay to determine the ER affinity for a large, structurally diverse group of chemicals. Uteri from ovariectomized Sprague-Dawley rats were the ER source for the competitive-binding assay. Initially, test chemicals were screened at high concentrations to determine whether a chemical competed with [3H]-estradiol for the ER. Test chemicals that exhibited affinity for the ER in the first tier were subsequently assayed using a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
433
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 717 publications
(472 citation statements)
references
References 67 publications
26
433
0
3
Order By: Relevance
“…All assays were repeated at least twice; the IC50 values of positive chemicals are the means of the replicate values. The standard deviation of IC50 for each chemical was reported (23), and only the mean RBA value was used for this study. The purity of chemicals as well as their effect on RBAs was also studied by Blair et al (23).…”
Section: Methodsmentioning
confidence: 99%
“…All assays were repeated at least twice; the IC50 values of positive chemicals are the means of the replicate values. The standard deviation of IC50 for each chemical was reported (23), and only the mean RBA value was used for this study. The purity of chemicals as well as their effect on RBAs was also studied by Blair et al (23).…”
Section: Methodsmentioning
confidence: 99%
“…Laboratory research has shown that a large number of different chemicals can exert estrogenic effects (Blair et al 2000;Legler et al 2000;Nishihara et al 2000;Houtman et al 2004b), including the natural estrogenic hormones 17b-estradiol, estriol and estrone, the synthetic estrogenic hormone and contraceptive pill ingredient 17a-ethynylestradiol, and phytoestrogens like isoflavonoides and coumestrol. Furthermore, various pesticides and industrial compounds, such as alkylphenols, alkylphenolethoxylates, and bisphenol A, which are applied as surfactants, plasticizers, and raw materials for the production of polycarbonate plastic, are estrogenic.…”
Section: Endocrine Disrupting Compoundsmentioning
confidence: 99%
“…EE2>E2>E3>E1 [29]. It is important to note that the present experiments were designed to evaluate the impact of the overall estrogenic activity of the MIX and the contribution of each individual compound is impossible to measure.…”
Section: Discussionmentioning
confidence: 99%